Characteristics of intestinal microbiota in preterm infants and the effects of probiotic supplementation on the microbiota - Yang, Sen; He, Jing; Shi, Jing; Xie, Liang; Liu, Yang; Xiong, Ying; Liu, Hanmin (Frontiers in Microbiology, 2024)
Objective In this study, we investigated the characteristics of the intestinal microbiota of preterm infants, and then analyzed the effects of probiotics supplementation on intestinal microbiota in preterm infants. Methods This study enrolled 64 infants born between 26 and 32 weeks gestational age (GA) and 22 full-term infants. 34 premature infants received oral probiotic supplementation for 28 days. Stool samples were obtained on the first day (D1) and the 28th day (D28) after birth for each infant. Total bacterial DNA was extracted and sequenced using the Illumina MiSeq Sequencing System, specifically targeting the V3-V4 hyper-variable regions of the 16S rDNA gene. The sequencing results were then used to compare and analyze the composition and diversity index of the intestinal microbiota. Results There was no significant difference in meconium bacterial colonization rate between premature and full-term infants after birth (p > 0.05). At D1, the relative abundance of Bifidobacterium, Bacteroides, and Lactobacillus in the stool of preterm infants was lower than that of full-term infants, and the relative abundance of Acinetobacter was higher than that of full-term infants. The Shannon index and Chao1 index of intestinal microbiota in preterm infants are lower than those in full-term infants (p < 0.05). Supplementation of probiotics can increase the relative abundance of Enterococcus and Enterobacter, and reduce the relative abundance of Escherichia and Clostridium in premature infants. The Chao1 index of intestinal microbiota decreased in preterm infants after probiotic supplementation (p < 0.05). Conclusion The characteristics of intestinal microbiota in preterm infants differ from those in full-term infants. Probiotic supplementation can reduce the relative abundance of potential pathogenic bacteria and increase the abundance of beneficial microbiota in premature infants.